Ecotoxicological effects of graphene oxide on the protozoan Euglena gracilis. (June 2015) - Hu, Changwei; Wang, Qing; Zhao, Haitao; Wang, Lizhi; Guo, Shaofen; Li, Xiuling
Graphical abstract: Graphene oxide on the cell surface can hinder the acquisition of the nutrition and light. Highlights: The 96 h EC50 value of graphene oxide in Euglena gracilis was 3.76 ± 0.74 mg L −1 . Graphene oxide exerted oxidative stress to the protozoa. Graphene oxide could inhibit the acquisition of nutrition and light. Abstract: Potential environmental risks posed by nanomaterials increase with their extensive production and application. As a newly emerging carbon material, graphene oxide (GO) exhibits excellent electrochemical properties and has promising applications in many areas. However, the ecotoxicity of GO to organisms, especially aquatic organisms, remains poorly understood. Accordingly, this study examined the toxicity of GO with protozoa Euglena gracilis as test organism. Growth inhibition test was initially performed to investigate acute toxic effects. Protozoa were subsequently exposed to GO ranging from 0.5 mg L −1 to 5 mg L −1 for 10 d. The growth, photosynthetic pigment content, activities of antioxidant enzymes, ultrastructure of the protozoa, as well as the shading effect of GO, were analyzed to determine the mechanism of the toxicity effect. Results showed that the 96 h EC50 value of GO in E. gracilis was 3.76 ± 0.74 mg L −1 . GO at a concentration of 2.5 mg L −1 exerted significant ( P < 0.01) adverse effects on the organism. These effects were evidenced by the inhibition of growth and the enhancement of malondialdehyde content and antioxidant enzyme activities. Shading effect and oxidative stress may be responsible for GO toxicity.